"An obese turtle on his back" – fat-shaming Donald J. Trump and the spectacle of fat masculinity. Issue 3 (2nd September 2022) - Kindinger, Evangelia
ABSTRACT: This article brings together fat studies and masculinity studies to critically read the various stagings of the fat body of former U.S. President Donald J. Trump in U.S. late-night talk shows such as Late Night with Seth Meyers, The Late Show with Stephen Colbert and Jimmy Kimmel Live! During his presidency, these and other late-night hosts stressed that Trump was unfit for office, a sentiment often supported by fat-shaming discourses and imagery of the spectacular transgressions of Trump's fat, male body that deemed his body as unfit for office as well. In these comedic segments, Trump's fat, male body was utilized as a visualization of his incompetence, failures, and moral shortfalls. As I argue, these fat-shaming discourses are not merely aimed at making visible Trump's lack of qualifications for the presidency, they result from deeply ingrained stigmatizations of fatness in popular culture. Specifically, I look at the unstable position of fat masculinity in U.S. public imagination, the dangers it supposedly poses to hegemonic masculinity, and the ways in which its intersection with whiteness (in this case Trump's whiteness) informs this position. Satire, as a specific kind of communication, functions as a catalyst for anti-fat attitudes that are presented as political commentary.